The wound microbiota: microbial mechanisms of impaired wound healing and infection - Uberoi, Aayushi; McCready-Vangi, Amelia; Grice, Elizabeth A (Nature reviews. Microbiology, 2024)
The skin barrier protects the human body from invasion by exogenous and pathogenic microorganisms. A breach in this barrier exposes the underlying tissue to microbial contamination, which can lead to infection, delayed healing, and further loss of tissue and organ integrity. Delayed wound healing and chronic wounds are associated with comorbidities, including diabetes, advanced age, immunosuppression and autoimmune disease. The wound microbiota can influence each stage of the multi-factorial repair process and influence the likelihood of an infection. Pathogens that commonly infect wounds, such as Staphylococcus aureus and Pseudomonas aeruginosa, express specialized virulence factors that facilitate adherence and invasion. Biofilm formation and other polymicrobial interactions contribute to host immunity evasion and resistance to antimicrobial therapies. Anaerobic organisms, fungal and viral pathogens, and emerging drug-resistant microorganisms present unique challenges for diagnosis and therapy. In this Review, we explore the current understanding of how microorganisms present in wounds impact the process of skin repair and lead to infection through their actions on the host and the other microbial wound inhabitants.